Die invloed van vaderafwesigheid op die kind (2014)
M.Ed. (Educational Psychology) === The absence of a father in family life is an occurrence which is experienced in almost every family. The absent-father refers to the father who, as a result of certain circumstances, cannot properly fulfill his role as father in the family circle. It appears that this phenomenon is gradually on the increase and it is apparent that parents increasingly feel the necessity to obtain guidance in respect of this particular problem. Several factors contribute towards the phenomenon of father-absence. The most general reason for this occurrence is the father's responsibility towards his occupation. The absent-father could also create the image of a father being physically present yet being psychologically absent. In this script an endeavour has been made to grasp the phenomenon of fatherly absence and the influence it could possibly have on a child. The purpose of this study is to determine, in the light of certain studies of literature and empirical research, the influence the fatherly absence has on a child. The purpose of this exercise is dual. Firstly it entails a literature study and secondly an empirical research. A relevant critical survey has been conducted in respect of the role the father plays in the family and in particular with special reference to the differential role of the father in the life of the son and daughter. The study of relevant literature further entails a critical study of fatherly absence and the influence it could have on the son and daughter.